Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Get accurate and detailed answers to your questions from a dedicated community of experts on our Q&A platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Answers:
a = 2
b = -1
c = 3
===========================================================
Work Shown:
(numerator)/(denominator) = quotient + (remainder)/(denominator
(2x^3-5x^2+4x-8)/(ax^2+bx+c) = x-2 + (bx-a)/(ax^2+bx+c)
2x^3-5x^2+4x-8 = (x-2)(ax^2+bx+c) + (bx-a)
2x^3-5x^2+4x-8 = x(ax^2+bx+c)-2(ax^2+bx+c) + (bx-a)
2x^3-5x^2+4x-8 = ax^3+bx^2+cx-2ax^2-2bx-2c + bx-a
2x^3-5x^2+4x-8 = ax^3+(bx^2+2ax^2) + (-2bx+cx+bx) + (-a-2c)
2x^3-5x^2+4x-8 = ax^3+(b+2a)x^2 + (-b+c)x + (-a-2c)
The x^3 term of the left hand side (LHS) is 2x^3, while the x^3 term of the right hand side (RHS) is ax^3. This must mean a = 2.
The x^2 term of the LHS is -5x^2. The x^2 term of the RHS is (b+2a)x^2
Plugging in a = 2 leads to (b+2a)x^2 turning into (b+4)x^2. Equating the two x^2 coefficients has us get b+4 = -5 solve to b = -1
Now focus on the x terms. The LHS has 4x and the RHS has (-2b+c)x. Plug in b = -1 to get (-b+c)x turn into (c+1)x. Set this equal to 4x and you should find that c = 3
-----------------
In summary, we have:
a = 2
b = -1
c = 3
Note how the last term on the RHS is -a-2c = -2-2(3) = -8 which matches with the last term on the LHS. This helps confirm we have the correct values for a,b,c. Further confirmation would involve polynomial long division.
Answer:
a = 2; b = -1; and c = 3
Step-by-step explanation:
If the quotient of [tex]2x^3-5x^2+4x-8[/tex] divided by [tex]ax^2+bx+c[/tex], gives [tex]x-2[/tex] , with a remainder of [tex]bx-a[/tex], then the product ( [tex]ax^2+bx+c[/tex], ) * ( [tex]x-2[/tex] ) plus [tex]bx-a[/tex] should equal: [tex]2x^3-5x^2+4x-8[/tex]
And we can investigate the values of a, b, and c via operating the product and afterwards identifying like terms as shown below:
[tex](x-2) * (ax^2+bx + c)+bx-a= ax^3 +bx^2+cx-2ax^2-2bx-2c+bx-a=\\=ax^3+(b-2a)x^2+(c-2b+b)x-2c-a=2x^3-5x^2+4x-8[/tex]
And therefore, making the coefficients of like terms equal, we get:
[tex]a = 2\\b-2a=-5;\,\,and\,\, b=-1\\c-b=4;\,\,and\,c=3\\-2c-a=-6-2=-8[/tex]
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.